Efektivitas Gallic Acid Sebagai Agen Antibakterial: Tinjauan Literatur - Fayza Nurhaliza Yasmine (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Gallic Acid (GA) is a polyphenolic compound widely found in plants and has shown potential as a natural antibacterial agent. This literature review aims to assess the effectiveness of gallic acid as an antibacterial based on available experimental studies. The reviewed articles include studies published between 2015 and 2025 that specifically investigated the antibacterial activity of gallic acid against pathogenic bacteria. Various studies have demonstrated that GA, either in its pure form or in combination with other materials such as hydrogels, gold nanoparticles (AuNP-GA), graphene oxide (GO-GA), and natural extracts, exhibits significant antibacterial activity against a wide range of bacteria, including Staphylococcus aureus, Escherichia coli, and other pathogenic bacteria. GA-based formulations also show additional benefits, such as promoting wound healing, supporting osteogenesis, and even exerting cytotoxic effects on certain cancer cells. Nevertheless, further research is needed to optimize the clinical application of gallic acid by considering both its safety and efficacy.